Disruption avoidance through the prevention of NTM destabilization in TCV. (29th August 2018) - Sheikh, U.A.; Duval, B.P.; Galperti, C.; Maraschek, M.; Sauter, O.; Sozzi, C.; Granucci, G.; Kong, M.; Labit, B.; Merle, A.; Rispoli, N.
Abstract: Destabilization of a stationary neoclassical tearing mode due impurity influx can lead to a potentially destructive disruption and is of significant concern for current and future tokamaks. A representative scenario was developed on TCV to experiment with applicable disruption avoidance techniques and produce a real time control system capable of handling such an event. Soft x-ray (SXR) radiation intensity and magnetic diagnostics analyses available in real time were used to provide plasma state information to the control system. Electron cyclotron current drive (ECCD) was employed to prevent NTM destabilization. Deposition of ECCD near the calculated q   =  2 surface was able to prevent destabilization of the NTM if a large increase in SXR radiation intensity was used as the trigger. A delay in avoidance resulted in the plasma entering a disruptive state which required over 100 ms of continuous ECCD around the q   =  2 surface to stabilize. Ramp down scenarios were studied to complete the design of a closed loop system. This system was then successfully tested using increasingly disruptive scenarios, through increased gas quantities, and the system was able to extend the discharge for a prescribed amount of time and safely ramp down the plasma current to the minimum controllable level. The system demonstrated in this work is presently limited to this specific type of disruption but this approach could be applied to other disruptive situations on the path to building a global disruption handling system.